Predictive technology in social media - Fernández Rovira, Cristina; Giraldo Luque, Santiago (CRC Press, 2022)
"Can the likes we give on Instagram and Facebook predict a purchase or foresee who will win the election? Yes, they can. Large digital platforms can target ads to hyper-segmented audiences to try to influence all of us. But, with the enormous power we have given them, will they be able to impose us certain behaviours or ideologies? Maybe yes. The book takes a critical look at how the predictive technology associated with social media works. They influence culture, politics, consumption, our leisure time, our attention span and even our health. It is the moment to think deeply about these technologies. As citizens, we must reflect on our digital future"- Resumé vydavatel
Keywords: sociální sítě; technologie -- sociologické aspekty; vliv médií; soukromí; social networks; media influence; technology -- sociological aspects; privacy; elektronické knihy; monografie; electronic books; monographs